THE MANAGEMENT OF PRE SCHOOL TOWARDS ACCREDITATION STANDARDS - selian, nurhaida (STAI Hubbulwathan Duri, 2019)
The research is conducted by the rampant growth of PAUD institutions in the regions but has not been accompanied by efforts to fulfill quality according to national quality standards so that they do not meet accreditation assessments. The objective of this research is to determine PAUD management system in national standards in Bengkalis District and to find out the dominant factors that do not meet national standards in PAUD management systems towards accreditation in Bengkalis District. The method of this reaearch is descriptive with using simple random technique. The data collection method is by observation and documentation. The results showed that the PAUD management system in Bengkalis District that fulfilled the national standard criteria passed the accreditation of 80% and 20% had not passed yet. The dominant factors that have not been fulfilled in the national standard criteria for PAUD management systems in Bengkalis District are: PAUD units do not yet have a personnel task description according to the organizational structure chart; PAUD unit does not have an annual work plan that contains elements of objectives, targets, policies, program activities, and financing; not enough aspects of development in the implementation of daily learning separately in the PAUD program; does not have a weekly activity plan; PAUD units does not yet have a holistic integrative program that includes health, nutrition, educational stimulation, care, and protection.